A conceptual article: The teachers’ role in implementing cognitive reading strategies to enhance students' reading comprehension - Pertiwi, Nestiti Lintang; Iftanti, Erna (Journal of English Language Teaching and Learning (JETLE), 2024)
The ability to read well is essential for learning English. Students' reading comprehension can be influenced by the application of efficient reading practices. Cognitive reading strategies are one method that can be used to enhance reading comprehension abilities. By using cognitive reading strategies, students can visualize information, absorb information in a predictable way, make connections between the text and prior knowledge, and evaluate their understanding. This study investigates the teacher's role in implementing cognitive reading strategies to improve students' reading comprehension abilities. This article uses a descriptive qualitative approach with a literature study design. Data was gathered through literature searches on Sinta, Google Scholar, Neliti.com, and ResearchGate. By arranging and summarizing research findings from several chosen articles, a descriptive analysis of the data was conducted. The findings indicate that the role of teachers is essential in helping students apply cognitive reading strategies to improve their reading comprehension skills, such as providing direction and guidance on reading strategies, modeling strategies, providing a supporting learning environment, activating students' prior knowledge, assisting and providing feedback to students, facilitating cooperative practice. However, this article only used secondary data so that the weakness of this article is the limited availability of related literature. Concerning the consequences, it is advised that future researchers might investigate deeper into the specific aspects that determine the successful implementation of cognitive reading strategies.